Penanaman Nilai-Nilai Sila II Pancasila pada Peserta Didik Kelas V Sekolah Dasar - Abduh, Muhammad; Taniredja, Tukiran (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2017)
The research objective was to determine (1) how the development of the values of the second principle of Pancasila on fifth graders; (2) what are the constraints of fifth grade teachers in developing the values of the second principle of Pancasila to the learners; (3) how the solution of sixth grade teachers to overcome the obstacles in developing the values of the second principle of Pancasila to the learners. Data were collected using an open questionnaire. Informants were the teachers of sixth graders. Data were analyzed using data reduction, the display data, the data conclusion/ drawing/ verification. To develop the values of the second principle of Pancasila on sixth graders are: (a) it will need habituation, awareness that human is a social beings; (b) the problem is the selfish attitude of learners do not cooperate with friends; (c) The solution is the realization that humans are social creatures, giving a good example, exchange student seat periodically. Keywords : values of the second principle of Pancasila, exemplary, habituaion, awareness, practice ABSTRAK Tujuan penelitian ini adalah untuk mengetahui: (1) cara-cara pengembangan nilai-nilai sila kedua Pancasila peserta didik kelas V sekolah dasar oleh guru kelas; (2) kendala para guru kelas V untuk mengembangkan nilai-nilai sila kedua Pancasila kepada para peserta didiknya; dan (3) solusi para guru kelas V untuk mengatasi kendala dalam mengembangkan nilai-nilai sila kedua Pancasila kepada para peserta didiknya. Data dikumpulkan dengan angket terbuka. Sebagai informan adalah guru-guru kelas V sekolah dasar Kabupaten Banyumas. Data dianalisis dengan data reduction, data display, data conclusion/drawing/verification. Hasil penelitian menunjukkan bahwa untuk mengembangkan nilai-nilai sila kedua Pancasila siswa kelas V diperlukan pembiasaan, penyadaran, pengamalan dan keteladanan. Kendalanya yaitu siswa masih bersifat egois dan kurang bekerja sama. Solusinya penyadaran bahwa manusia adalah makhluk sosial, pemberian suri teladan yang baik, dan penukaran tempat duduk siswa secara periodik. Kata kunci: sila kedua Pancasila, keteladanan, pembiasaan, penyadaran, pengamalan